The Influence of Genre Understanding on Strategy Use and Comprehension - Yoo, Monica S (Journal of adolescent & adult literacy, 2015)
This case study examines how Ashley, a ninth-grade student, uses and applies metacognitive strategies for comprehension as she reads three different texts: a literary narrative, a history text, and a newspaper article. Interviews and think-aloud protocols were administered to investigate how the student thought about and enacted a variety of strategies during reading. The study includes cognitive and sociocultural perspectives and applies genre theory to the literature on reading strategies and the reading process. Findings indicate that expectations regarding how to read in a genre and discipline may influence comprehension and the ways in which strategies are employed. Furthermore, implications suggest that it is important to consider how genre understandings impact key elements related to comprehension in the Common Core State Standards, such as the quantitative and qualitative components of text complexity and the reader--text fit, as students engage in reading in a variety of disciplines.